PENGARUH REAKSI PASAR ATAS PENGUMUMAN INFORMASI LABA PERUSAHAAN BERKAITAN DENGAN MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Theresia Sri Hastuti; Henilia Yulita (Business Management Journal, 2017)
Financial report is an important factor for inventors to make investment decision in capital market. Publicly financial report which has relevant information will be reacted by market player. Many investors and other users of financial report do not pay attention to the process of publishing financial report, so it pushes the emergence of dysfunctional behaviours like earning management practices.The research aims to analyze the difference of market reaction between:1) earning management companies and non-earning management companies; 2) income-decreasing discretionary accruals companies and income-increasing discretionary accruals companies.Population of this research is 130 manufactured companies listed in JSX during 2009-2010. Using convenience sampling method, 49 companies were taken to become final samples for each period. The result with two independent samples test Kruskal Walles χ (sign 5%) shows that there was no difference of market reaction between earning management companies and non-earning management companies (χ 0,58989 dan 0,03137), and neither was there between income-decreasing discretionary accruals companies and income-increasing discretionary accruals companies (χ 0,735 dan 2,82767).Keywords : Earning Management, Market Reaction.